ANALISIS POSTUR KERJA PADA STASIUN STERILIZER DENGAN MENGGUNAKAN METODE OWAS DAN REBA - Yusi Hidjrawan; Aman Sobari (Universitas Teuku Umar, 2018)
Work posture analysis needs to be done in order to reduce injuries, Musculoskeletal Disorders are one of the injuries that are often experienced by workers in carrying out Manual Material Handling (MMH) activities, namely injuries to muscles, nerves, tendons, bones, joints, cartilage caused by activities work. The purpose of this study was to measure work posture using the OWAS and REBA methods. These results will be used as a reference to provide recommendations for improving working posture at the Sterilizer station. The results of this study indicate that there is no significant difference in evaluating work posture in assessing work posture with the application of OWAS and REBA methods. Only the final score (grand score) is different, this is because the assessment of the assessment category scores on each work element is different based on the method used. Assessment of posture based on the OWAS and REBA methods provides the same conclusion that the level of risk of musculoskeletal disorders is at a high level. This proves that both relevant methods are used to assess at the sterilization station at PT. Karya Tanah Subur.